Plate osteosynthesis after patellar fracture: 1-year results of a prospective study. Issue 4 (27th April 2017) - Ellwein, Alexander; Katthagen, Jan; Jensen, Gunnar; Lill, Helmut; Raschke, Michael
Aims and Objectives: Tension band wiring after patellar fractures is associated to a high number of implant related complications (22-53%). Revision surgery is necessary in 10-55% of the patients with mostly unsatisfactory results. The patella plate is an alternative treatment with the advantages of a locked plating implant. Biomechanical studies have shown a significant higher stability compared to tension band wiring. Therefore an immediate full weight bearing after surgery is allowed with the prophylaxis of knee-stiffness. The purpose of this study was to evaluate the first time clinical prospective results and complications of this new implant. Materials and Methods: Between April 2013 and May 2015 all patients that were treated with locked plating for patella fractures were included in this prospective study. Patients were examined after 6 weeks, 6 and 12 months. Information about patient satisfaction, pain situation and the functional result were collected. Additionally subjective scores (Tegner activity score, Lysholm-score, Kujala-score) were determined and compared to their value before trauma. Complications and revision surgeries were recorded and analysed. Results: 17 patients, 6 women and 11 men, with a mean age of 58 (19-87) years were included in this study. The range of motion of the injured knee was 120° after 6 weeks and improved to 138° after 6 months, corresponding to 84% and 97% of the range of motion of the healthy opposite knee. The Tegner activity scale increased from 2, 5 to 3, 5 (initial value: 4), the Lysholm score from 78 to 92 points (initial value: 97) and the Kujala score from 72 to 88 points (initial value: 96). Two complications occurred: one patient had a reactive bursitis praepatellaris and one patient sustained a loss of reduction. Another two patients had their implants removed. Patient satisfaction reached 94% after one year. Conclusion: Locked plating of patella fractures is a reliable alternative treatment with good functional outcomes, low complication rates and high patient satisfaction. Already 6 months after surgery the functional results and subjective scores reached results as before trauma. Furthermore the aftercare with immediate full-weight bearing and motion exercise improves quality of life through an early return to daily life.